A standardised comparison of chest and percutaneous drainage catheters to evaluate the applicability of the ‘French’ sizing units - Karan Daga; Graham D. Milward; Daniel Pintos dos Santos; Derek W. Edwards; Hans-Ulrich Laasch (Scientific Reports)
Abstract A variety of medical specialities undertake percutaneous drainage but understanding of device performance outside radiology is often limited. Furthermore, the current catheter sizing using the “French” measurement of outer diameter is unhelpful; it does not reflect the internal diameter and gives no information on flow rate. To illustrate this and to improve catheter selection, notably for chest drainage, we assessed the variation of drain performance under standardised conditions. Internal diameter and flow rates of 6Fr.-12Fr. drainage catheters from 8 manufacturers were tested to ISO 10555-1 standard: Internal diameters were measured with Meyer calibrated pin-gauges. Flow rates were calculated over a period of 30s after achieving steady state. Evaluation demonstrated a wide range of internal diameters for the 6Fr., 8Fr., 10Fr. and 12Fr. catheters. Mean measurements were 1.49 mm (SD:0.07), 1.90 mm (SD:0.10), 2.43 mm (SD:0.11) and 2.64 mm (SD:0.03) respectively. Mean flow rates were 128 mL/min (SD:37.6), 207 mL/min (SD: 55.1), 291 mL/min (SD:36.7) and 303 mL/min (SD:20.2) respectively. There was such variance that there was overlap between catheters of different size: thin-walled 10Fr. drains performed better than 12Fr. “Seldinger” chest drains. Better understanding of drain characteristics and better declaration of performance data by manufacturers are required to allow optimum drain choice for individual patients and optimum outcomes.